Mediating Role of Military Professionalism in The Effect of Spiritual Leadership and Work Motivation on Soldier Performance - Amanda, Randhika Deryl (Jurnal Ilmiah Administrasi Publik, 2022)
In military organizations, the concept of soldier performance is the most important thing that is strategic and tactical. The purpose of this study was to examine the mediating role of military professionalism on the influence of spiritual leadership and work motivation on soldier performance. The social learning theory used as a theoretical foundation to build a conceptual framework that was proposed in this study. About 150 of 168 Non-Commander Officer (CFO) of Indonesian Army located in Malang, especially who work in Batallion Arhanud 2/ABW/2 Kostrad Malang are taken as sample of this study. SmartPLS is used as analysis tool to examine the direct and indirect effect among observed variables. The results showed that one of the five paths of influence on the relationship between variables was found to be insignificant, namely the direct influence of spiritual leadership on soldier performance. While results indicate that spiritual leadership could not directly affect individual performance, it also reveals about important mediating role of military professionalism in order to increase the effect of spiritual leadership and work motivation on soldier performance.